Upaya Pemerintah Dalam Memfasilitasi Pembangunan Kebun Masyarakat Di Kabupaten Blitar (RechtJiva, 2024)
This study aims to evaluate the effectiveness of regulations requiring plantation companies in Blitar Regency to allocate 20% of their cultivated land for community plantations. The research methodology includes in-depth interviews with relevant parties, such as the Blitar Regency Government, the Blitar Regency Agriculture and Food Office, the East Java Regional Office of the National Land Agency, and the local community. Data analysis is conducted using Lawrence M. Friedman's legal effectiveness theory, which encompasses three main components: legal structure, legal substance, and legal culture. The findings indicate that out of 12 operating companies in Blitar Regency, only one company complies with the regulation. The main obstacles identified in implementing this regulation include inadequate coordination and effective oversight by the government, non-compliance by companies, and insufficient understanding and limited dissemination of the regulations to the community. Additionally, the study found overlapping issues between plantation laws and land use rights decisions issued by the East Java BPN, further complicating the regulation's implementation. The local community expresses a strong desire for companies to adhere to the regulations, but there are misunderstandings regarding the implementation of these rules among the public. Based on these findings, the study recommends several improvements, including enhanced coordination and oversight by the government, stricter enforcement of laws against non-compliant companies, and increased efforts in socialization and education for the community. It is hoped that these measures will significantly enhance the effectiveness of the regulations in Blitar Regency, thereby better achieving the regulation's initial objectives.